5 - Electoral Politics and Election Outcomes in Kenya: by Peter Wanyande - Wanyande, Peter (Africa Development, 2006)
Kenya has held presidential, parliamentary and local government elections every five years since independence in 1963 in accordance with the country’s constitution. For most of the independence period the country operated a one party system of government. This was brought to an end in 1992 when the coun- try reverted to multi party democracy following an amendment to the relevant section of the presidential and National Assembly Elections Act. The change from one party to multi party system affected both the administration and legal environments in which elections occurred. Other factors that affected elections include ethnicity, clanism, nature of political parties, personality of individual politicians and in some cases religion. Voter turn out has been particularly high during multi party era and particularly more during the elections of 2002. This was due to two factors. First was the opposition unity prior to the elections and secondly the fact that Kenyans had the opportunity to elect a new president after 24 years of rule by President Moi. Moi had served his last term in accordance with the changes made to the relevant provisions of the presidential Elections Act in 1992, which for the first time limited presidential term to two five-year terms. Future elections are likely to be influenced by similar complex factors discussed in this paper.